2017
DOI: 10.1097/igc.0000000000000716
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Pathological Outcomes of Laparoscopic Versus Abdominal Radical Hysterectomy With Pelvic Lymphadenectomy and/or Para-aortic Lymph Node Sampling for Bulky Early-Stage Cervical Cancer

et al.

Abstract: The surgical outcomes of LRH with pelvic lymphadenectomy and/or para-aortic lymph node sampling exhibited a similar therapeutic efficacy to those of the ARH approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…10,11 Over the last 2 decades, multiple retrospective studies comparing the oncologic outcomes of MIS to those of open radical hysterectomy for the treatment of early-stage cervical cancer have reported similar rates of recurrence, death, disease-free survival (DFS), and overall survival (OS). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, two recent publications reported worse survival outcomes with MIS compared with laparotomy, raising concerns over the MIS approach. In a large epidemiologic retrospective national cancer database (NCDB) study in the US, Melamed et al reported shorter OS with MIS over open radical hysterectomy among patients with earlystage cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Over the last 2 decades, multiple retrospective studies comparing the oncologic outcomes of MIS to those of open radical hysterectomy for the treatment of early-stage cervical cancer have reported similar rates of recurrence, death, disease-free survival (DFS), and overall survival (OS). [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, two recent publications reported worse survival outcomes with MIS compared with laparotomy, raising concerns over the MIS approach. In a large epidemiologic retrospective national cancer database (NCDB) study in the US, Melamed et al reported shorter OS with MIS over open radical hysterectomy among patients with earlystage cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were no reports showing an accurate rate of an internal hernia caused by a vascular structure, it is considered to be extremely rare. In contrast, pelvic lymph node dissection has been a standard procedure for patients with prostate cancer [1], bladder cancer [2], ovarian cancer [3], and cervical cancer [4]. ePLND isolates the vessels from neighboring tissues, thus creating a potential hernial defect.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic lymph node dissection is a standard procedure in many operative treatments in cancer, such as prostate cancer [1], bladder cancer [2], ovarian cancer [3], and cervical cancer [4]. Also, a Japanese multi-institutional study clarified that extended pelvic lymph node dissection (ePLND) with skeletonization of the external iliac artery improved staging and removed a greater number of metastatic nodes in prostate cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…Since originally reported by Minelli in 1990,16 LRH has been increasingly adopted in the treatment of CC during the past few decades. A lot of studies suggested that LRH was associated with no difference in oncologic outcomes as compared with the ARH,5,11,12 and several studies revealed that LRH had better survival outcomes than the open approach 7,10. Recently, a prospective, randomized trial13 indicated that patients who underwent minimally invasive radical hysterectomy for early-stage CC had lower rates of DFS and OS than patients who underwent open ARH.…”
Section: Discussionmentioning
confidence: 99%
“…Although laparoscopic radical hysterectomy (LRH) has been widely adopted in CC patients over the past few decades, the oncologic safety of LRH in treating CC patients compared with abdominal radical hysterectomy (ARH) remains questionable 58. Several studies have demonstrated that neither LRH nor ARH had a significant impact on the survival outcomes in patients with early-stage CC 912. However, a recent prospective, randomized trial showed that minimally invasive radical hysterectomy was associated with lower rates of disease-free survival (DFS) and overall survival (OS) than open ARH among women with early-stage CC 13.…”
Section: Introductionmentioning
confidence: 99%